Osteological description of the Andean puma (Puma concolor): II. Axial skeleton - Zapata, Celso (2019)
Two axial skeletons of puma (Puma concolor), one male and one female, that were confiscated in the province of Canchis (Peru) and ceded to the IVITA Research Centre under the Temporary Custody Act No. 01-2015-SERFOR-ATFFS-Cusco were used through the research authorization N° 158-2015-SERFOR-DGGSPFFS. The standard method for the dissection of the skeleton was applied and the terms used are in accordance with the Veterinary Anatomical Terminology. The measurements were made with a calliper. At the level of the skull and jaw, the eminences and depressions related to the origin and insertion of muscles stand out, such as the nuchal crest, sagittal crest, the masseteric fossa and the parietal fossa. The vertebral column resembles that described in cats, except for certain particularities that are more prominent, such as the accessory process and the mamillary process. At the level of the thoracic vertebrae, the anticlinal vertebra is T11, this having a shorter spinous process. The ribs and the sternum follow the patterns described for other felines.